2018
DOI: 10.3389/fmicb.2018.00399
|View full text |Cite
|
Sign up to set email alerts
|

Unique Microbial Diversity and Metabolic Pathway Features of Fermented Vegetables From Hainan, China

Abstract: Fermented vegetables are typically traditional foods made of fresh vegetables and their juices, which are fermented by beneficial microorganisms. Herein, we applied high-throughput sequencing and culture-dependent technology to describe the diversities of microbiota and identify core microbiota in fermented vegetables from different areas of Hainan Province, and abundant metabolic pathways in the fermented vegetables were simultaneously predicted. At the genus level, Lactobacillus bacteria were the most abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
3
36
1
Order By: Relevance
“…The microbial metabolism of carbohydrate, lipids, and proteins produce the complex compounds which form the sensory properties of fermented food (Liang et al, 2018b). Previous research had reported that carbohydrate metabolism, amino acid metabolism, nucleotide metabolism, and energy metabolism were the main pathways in metabolism (Liang et al, 2018a,b;Peng et al, 2018). Our results agreed with these findings, indicating that the top 3 pathways were carbohydrate metabolism, amino acid metabolism, and energy metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…The microbial metabolism of carbohydrate, lipids, and proteins produce the complex compounds which form the sensory properties of fermented food (Liang et al, 2018b). Previous research had reported that carbohydrate metabolism, amino acid metabolism, nucleotide metabolism, and energy metabolism were the main pathways in metabolism (Liang et al, 2018a,b;Peng et al, 2018). Our results agreed with these findings, indicating that the top 3 pathways were carbohydrate metabolism, amino acid metabolism, and energy metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…In our study the microbial community structure in different samples showed no significant differences in α- and β- diversity; however, the dominant genera were variable. This contradicts with the results of the microbial profiles reported in other fermented vegetables, which significantly differed based on their region of origin and raw materials used ( Peng et al, 2018 ). The results of difference analysis concerning the abundance of predominant genera in the five samples are depicted in Figure 3 .…”
Section: Resultscontrasting
confidence: 95%
“…Moreover, the various index values of fermented cabbage were significantly higher than those of the other three fermented vegetables, implying that the microbial diversity and uniformity of the fermented cabbage was the highest (Peng et al . ). This present study offered five‐day dynamic data based on the abovementioned statistical indexes (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, Lactobacillus bacteria were also the most abundant genus in fermented vegetables in Hainan province of China regardless of the sampling regions and vegetable species (Peng et al . ). Several prevalent LAB genera in kimchi, such as Leuconostoc , Weissella and Pediococcus (Chang and Chang ; Jeong and Lee ) were present in this research but never dominated during the fermentation process, probably because of their weaker resistance to acidity, origination from other raw materials (such as garlic or onions) or failure in competition for nutrients with Lactobacillus .…”
Section: Resultsmentioning
confidence: 97%